Examining convalescent plasma transfusion in severe COVID-19 patients, recent research highlights the significance of S-RBD antibodies and IL-10 levels - Etnawati Putri, Aditea; Agustina Tambunan, Betty; Pujo Semedi, Bambang; Mohd Yusoff , Narazah; Salmah Bt Noordin, Siti (Indonesian Journal of Tropical and Infectious Disease, 2023)
Convalescent plasma (CP) may be an option for people with severe COVID-19. However, its efficiency remains unknown. A study was done to determine whether the levels of Anti-SARS-CoV-2 Spike Receptor-Binding Domain (S-RBD) antibodies and IL-10 in COVID-19 patients who had CP transfusion were related to their survival status. The observational cohort study included 40 patients with severe COVID-19 who were followed for 28 days after receiving a CP transfusion. Antibody and IL-10 levels were assessed on Day 1 before to CP transfusion and on Days 1, 2, and 7 following CP transfusion. Twenty six (65%) of the 40 patients survived. Anti-SARS-CoV-2 S-RBD antibody levels were observed to be significantly higher on Days 1, 2, and 7 following CP transfusion (p-value 0.05). Furthermore, IL-10 levels dropped significantly on Days 2 and 7 (p-value 0.05). However, neither the CT value nor the patients' survival status were linked to greater antibody levels or changes in IL-10 levels. According to the findings, CP transfusion can greatly enhance anti-SARS-CoV-2 S-RBD antibody levels while drastically decreasing IL-10 levels. These findings may have therapeutic implications for the use of CP as a COVID-19 therapy option. More research is needed to determine its efficacy in enhancing the survival rate of COVID-19 patients with severe symptoms.